2019
DOI: 10.1093/scan/nsz044
|View full text |Cite
|
Sign up to set email alerts
|

Vocal threat enhances visual perception as a function of attention and sex

Abstract: This pre-registered event-related potential study explored how vocal emotions shape visual perception as a function of attention and listener sex. Visual task displays occurred in silence or with a neutral or an angry voice. Voices were task-irrelevant in a single-task block, but had to be categorized by speaker sex in a dual-task block. In the single task, angry voices increased the occipital N2 component relative to neutral voices in women, but not men. In the dual task, angry voices relative to neutral voic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(74 reference statements)
0
3
1
Order By: Relevance
“…Thus, subtle differences in how the pandemic was handled nationally as well as other interindividual variables could be relevant in modulating psychophysical responses to touch. Although, the present and previous research, in various cultures, has shown that the inverted u-shaped pleasantness is relatively stable on a group level (Croy et al, 2021; Cruciani et al, 2021; Schirmer et al, 2019), variables such as touch frequency, touch manners, or current ideology have been linked to the feelings elicited by touch (Sailer & Ackerley, 2019; Schirmer, Cham, et al, 2022; Sorokowska et al, 2021). Future research is required to understand whether and how these variables moderate the effect of velocity and other motion properties on the subjective evaluation of stroking touch.…”
Section: Discussioncontrasting
confidence: 70%
“…Thus, subtle differences in how the pandemic was handled nationally as well as other interindividual variables could be relevant in modulating psychophysical responses to touch. Although, the present and previous research, in various cultures, has shown that the inverted u-shaped pleasantness is relatively stable on a group level (Croy et al, 2021; Cruciani et al, 2021; Schirmer et al, 2019), variables such as touch frequency, touch manners, or current ideology have been linked to the feelings elicited by touch (Sailer & Ackerley, 2019; Schirmer, Cham, et al, 2022; Sorokowska et al, 2021). Future research is required to understand whether and how these variables moderate the effect of velocity and other motion properties on the subjective evaluation of stroking touch.…”
Section: Discussioncontrasting
confidence: 70%
“…Our sample contained mostly female participants, and generalizing our findings to males should be taken with care since previous work has suggested sex differences with respect to the processing of emotional information (for a review, see Kret and De Gelder, 2012 ). Regarding ERPs, women exhibit larger mid-latency modulations for emotional vocalizations ( Schirmer et al., 2019 ) and larger LPP responses to images conveying interpersonal touch in implicit tasks ( Schirmer and McGlone, 2019 ) and show task-modulated N170 emotion effects ( Valdés-Conroy et al., 2014 ). Furthermore, each emotional expression was repeated 6 times and each identity even 12 times in total.…”
Section: Discussionmentioning
confidence: 99%
“…Singapore has a dominantly Chinese population and uses English as its official language. The sample size for this study was based on prior research exploring individual differences in voice perception [6,47]. Participants of this study were Singaporean residents who PLOS ONE spoke English as their native language.…”
Section: Participantsmentioning
confidence: 99%